Projections of Spring Wheat Growth In Alaska: Opportunity and Adaptations in a Changing Climate ... - Harvey, Stephen (Mendeley, 2021)
This dataset is part of the the paper "Projections of Spring Wheat Growth in Alaska: Opportunity and Adaptations in a Changing Climate" written by Harvey et al. (2021) and published in Climate Services. The research question for this dataset was: How will climate change impact the growth of spring wheat in Fairbanks, Alaska? The DSSAT CERES-Wheat crop simulation model was used to answer this question. Data consists of DSSAT V4.7.0.0 files, field data from 2011-2018, 1989-2018 weather, and 2020-2099 climate projections. The 2011-2017 field dataset is from variety trials and the 2018 field dataset was collected for the purpose of crop modeling. In the Field Data files, 2011-2018 plant and soil data was collected at the University of Alaska Fairbanks small grains variety trial plot in Fairbanks, AK. Weather data was collected at the Fairbanks Experiment Farm weather station. Climate projections were provided by University of Alaska Fairbanks, Scenarios Network for Alaska + Arctic Planning. Field data was input ...